Sustainability of forest bioenergy in Europe: land‐use‐related carbon dioxide emissions of forest harvest residues. Issue 4 (18th March 2014) - Repo, Anna; Böttcher, Hannes; Kindermann, Georg; Liski, Jari
Abstract Increasing bioenergy production from forest harvest residues decreases litter input to the soil and can thus reduce the carbon stock and sink of forests. This effect may negate greenhouse gas savings obtained by using bioenergy. We used a spatially explicit modelling framework to assess the reduction in the forest litter and soil carbon stocks across Europe, assuming that a sustainable potential of bioenergy from forest harvest residues is taken into use. The forest harvest residue removal reduced the carbon stocks of litter and soil on average by 3% over the period from 2016 to 2100. The reduction was small compared to the size of the carbon stocks but significant in comparison to the amount of energy produced from the residues. As a result of these land‐use‐related emissions, bioenergy production from forest harvest residues would need to be continued for 60–80 years to achieve a 60% carbon dioxide (CO2) emission reduction in heat and power generation compared to the fossil fuels it replaces in most European countries. The emission reductions achieved and their timings varied among countries because of differences in the litter and soil carbon loss. Our results show that extending the current sustainability requirements for bioliquids and biofuels to solid bioenergy does not guarantee efficient reductions in greenhouse gas emissions in the short‐term. In the longer‐term, bioenergy from forest harvest residues may pave the way to low‐emission energy systems.